Food store environment examination – FoodSee: a new method to study the food store environment using wearable cameras. (September 2020) - McKerchar, Christina; Smith, Moira; Stanley, James; Barr, Michelle; Chambers, Tim; Abel, Gillian; Lacey, Cameron; Gage, Ryan; Ni Mhurchu, Cliona; Signal, Louise
Introduction: Food environments shape food behaviours and are implicated in rising rates of obesity worldwide. Measurement of people's interactions with food stores is important to advance understanding of the associations between the food environment and in-store behaviour. This paper describes a new method, Food Store Environment Examination (FoodSee) to measure people's interaction with the food store environment in a feasibility study focused on convenience stores and children. Methods: One hundred and sixty-eight randomly selected children (aged 11–13 years) recruited from 16 randomly selected schools in Wellington, New Zealand, used wearable cameras for 4 days that recorded images every 7 s. The study was conducted from July 2014 to June 2015. All images of convenience stores and service stations, and a sample of images from supermarkets, were evaluated to determine the feasibility of assessing food availability and marketing. The outcomes of interest assessed were: food product availability, placement, packaging, branding, price promotion, purchases and consumption. Results: Thirty-seven children (22%) visited a convenience store or service station at least once during the study period. In total, there were 65 visits to 34 different stores. Seven hundred and nineteen images revealed the in-store environment. Of those, 86.1% were usable and able to be analysed for the outcomes of interest. Conclusions: The FoodSee methodology provides a promising new method to study people's interaction with the in-store food environment. The evidence generated will be valuable in understanding and improving the food store environment within which people shop, and will contribute to efforts to address obesity globally.